PELATIHAN PENGGUNAAN APLIKASI GEOGEBRA PADA MATERI PERSAMAAN GARIS LURUS - Arfany, Fenny Putri; Surahmat; Fuady, Anies (Universitas Djuanda, 2024)
The background for this community service activity is Pakis Islamic Middle School, which is one of the schools that has not yet implemented too many ICT-based learning models. This is due to the lack of projector facilities provided in each class as a medium for implementing ICT-based learning models. One learning model that is suitable to be applied based on the material being studied is to use the Geogebra application. Students can see the interpretation of graphs through the application. This service activity is carried out using the training method for trainees who are studying straight line equations. During the activity, monitoring was also carried out by the service team and evaluation through the results of test scores and questionnaires. The result of this community service activity is that the test results of the trainees found an average of 83.2. From this average, the training can be said to be successful because it is above the KKM standard in mathematics. While the value of the questionnaire was found that 92% of the training participants gave a positive response to using the Geogebra application on straight line equations. The advantages that trainees find are graphs that can be generated quickly, the GeoGebra application can provide a clearer visual experience to trainees in understanding mathematical concepts, can be used as an evaluation to ensure that the graphs that have been made are correct.